Academic Stress as a Trigger Factor for Migraine in College Students: A Literature Review - Yudhisman Imran; Akialyn Naznin Sorfina (Journal of Society Medicine, 2026)
Migraine is a common primary headache disorder among college students and is strongly associated with impaired academic performance and a reduced quality of life. Students are a particularly vulnerable population owing to their sustained exposure to academic demands, irregular lifestyles, and poor sleep. Among the many reported precipitants, academic stress is one of the most frequently cited triggers of migraine attacks; however, its contribution is shaped by multiple interacting factors. This narrative literature review synthesizes the current evidence on the relationship between academic stress and migraine in college students, integrating epidemiological, pathophysiological, and psychosocial perspectives. The reviewed literature indicates that migraine is a multifactorial disorder involving neurovascular mechanisms, genetic predisposition, hormonal influences, lifestyle, and psychological factors. Academic stress arises from examinations, assignments, time pressure, and performance expectations, and higher stress levels are consistently associated with a greater frequency and severity of attacks. Prolonged stress may activate the sympathetic nervous system and hypothalamic–pituitary–adrenal axis, producing hormonal changes and heightened pain sensitization. Lifestyle factors common among students, such as poor sleep quality, irregular meals, dehydration, and limited physical activity, further amplify migraine vulnerability. However, some studies have reported inconsistent associations, indicating that academic stress is not an isolated determinant. Overall, academic stress contributes meaningfully to migraine, particularly when combined with poor sleep and unhealthy lifestyles; however, migraine ultimately results from complex biological, psychological, and environmental interactions. Therefore, preventive strategies should adopt a holistic approach encompassing stress management, lifestyle modification, and psychosocial support within academic settings.